Jean Muno, témoin de son temps - Bizek-Tatara, Renata (Wydawnictwo Naukowe UAM, 2012)
Jean Muno is the writer who does not introduce History into his fiction until his penultimate work – "L’histoire exécrable d’un héros brabançon" (1982). The autobiographical novel shows, very often in a humoristic or even ironical way, the most important events of the years 1925 – 1981: World War I, the Prague Spring, the May of ‘96 and the Belgian language and identity issues. Muno gives up the humorous tone only when he writes about the Belgian unitary problem and he does it in an oblique way by introducing the secondary character of Madame Eendracht – an evident personification of Belgium. Her appearance indicates significant stages of the country’s historical evolution and allows the reader to track the institutional changes of the 1920s till the reform in 1980, which puts an end to the unitary state and makes Belgium a multiethnic and multilingual federal country.
Jean Muno, the witness of his times
Keywords: Jean Muno; History; Institutional changes; Personification of Belgium; Humorous